STRATEGI PEMBELAJARAN BAHASA INDONESIA DI ERAKURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) - Ridwan Laki (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2018)
The purpose of writing this article is to improve knowledge about the Indonesian Language Learning Strategy which can be useful for all parties in the future. This research uses literature review with data collection technique by using existing literature books. This article attempts to describe the concept of Indonesian language learning strategies using a learning approach, learning methods and techniques that are in accordance with the Education Unit Level Curriculum through the author's argument. The results of the literature review found that the learning management strategy is a component of the variables methods that deal with how the interaction between student with any other variables method. This Strategy relating to decision about organizational strategies and spesific delivery strategies used during the learning process. There are four classifications of variables strategies of learning management which include (1) scheduling the using of learning strategies, (2) making notes on student learning progress, and (3) motivational management, and (4) learning control. From the description above, it can be conclude in order to make indonesian language learning in the classroom interesting, so the teacher is expected to be able to carry out learning by applying/using appropriate learning strategies (methods and techniques). The strategy that must be adjusted to the basic competency and learning Indicators by involving students maximally learning activity.